Tafsir Ibnu Katsir - Diana Risky Harahap; Luthfiah Nailatul Izzah; Riska Sawitry (PT. Hasba Edukasi Mandiri, 2026)
The Tafsir Ibn Kathir is a monumental work in the study of Quranic exegesis, written by Imam Ibn Kathir. This tafsir is known as the tafsir bil ma'tsur method, namely the interpretation of the Quran based on the Quran itself, the hadith of the Prophet, the opinions of the Companions, and the followers of the Prophet. This study aims to examine the characteristics, methods, and advantages of the Tafsir Ibn Kathir in understanding the meaning of Quranic verses. The method used is a literature study by analyzing the contents of the Tafsir Ibn Kathir book and related sources. The results of the study indicate that the Tafsir Ibn Kathir excels in its thoroughness in the chain of hadith, systematic explanation of the verses, and the use of strong narrations as a basis for interpretation. Furthermore, this tafsir also provides explanations of language and historical context that help readers understand the verses' meanings comprehensively. However, several Israeli narrations are included with critical explanations.